The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/mbio.00819-21
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Clones Produce SARS-CoV-2 That Causes Severe Pulmonary Disease in Infected K18-Human ACE2 Mice

Abstract: Newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the ongoing coronavirus disease 2019 (COVID-19) pandemic, which has caused extensive mortality and morbidity and wreaked havoc on socioeconomic structures. The urgent need to better understand SARS-CoV-2 biology and enable continued development of effective countermeasures is aided by the production of laboratory tools that facilitate SARS-CoV-2 research. We previously created a directly accessible SARS-CoV-2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Although live ancestral SARS-CoV-2 was not detected at 6 dpi in the brain tissue, the lesions identified in the brain of ancestral strain-infected mice indicate that virus may be replicating at very low levels or being cleared earlier than the Delta strain. Previous studies have identified live virus in the brain of K18-hACE2 mice infected with the ancestral strain at similar disease time points as those analyzed here ( 43 ). Further assays to determine virus growth and histopathology of brain tissue at earlier and later time points would help clarify if virus replication correlates with brain pathology.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although live ancestral SARS-CoV-2 was not detected at 6 dpi in the brain tissue, the lesions identified in the brain of ancestral strain-infected mice indicate that virus may be replicating at very low levels or being cleared earlier than the Delta strain. Previous studies have identified live virus in the brain of K18-hACE2 mice infected with the ancestral strain at similar disease time points as those analyzed here ( 43 ). Further assays to determine virus growth and histopathology of brain tissue at earlier and later time points would help clarify if virus replication correlates with brain pathology.…”
Section: Discussionsupporting
confidence: 66%
“…SARS-CoV-2-ancestral strain (GenBank accession no. NC_045512.2 , MN908947.3 ) was generated as previously described ( 43 , 68 ). Briefly, 10 μg of pCC1-4K-SARSCoV-2-Wuhan-Hu1 (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse #F2 regained its original weight and mobility by 9 dpi, while mouse #F1 was still 10% below its original weight and no amelioration of the clinical condition at 14 dpi. The results showing early weight loss in DRAGA mice at 1 dpi are in agreement with studies in SARS-CoV-2 infected human ACE2 transgenic mice, which also showed 5–10% body weight loss at 1 dpi and attributed to severe dehydration 52 , 53
Figure 4. Dynamics of body weight changes following SARS-CoV-2 infection of HIS-DRAGA mice.
…”
Section: Resultssupporting
confidence: 89%
“…(2021) made use of the k18-hACE2 model to better understand the effect of SARS-CoV-2 infection on lung and GI microbiome diversity, an important factor in the immune system of infected hosts. Additionally, Liu et al. (2021) used this model when they reverse-engineered SARS-CoV-2 clones that could be used to further understand viral pathogenesis, as well as COVID-19 variants.…”
Section: Animal Models Of Covid 19mentioning
confidence: 99%